The Impact of Endowments on Scientific Research and Cultural Development: A Model of Endowments in Universities (مجلة وقف في دراسات الاوقاف, 2026)
This research aims to discuss a type of endowment, specificallythe models of the Waqf University, which today serves as a paradigmfor modern education and a model for social advancement. Theresearcher illustrates the impact of endowment on scientificresearch and cultural development. The university has a close– Prevention of dividing the superintendents’ tasks and functionsregarding the endowment if joint supervision is assigned tothem.– Justice among the children in the endowment, as in other gifts.– Division annulment due to the extinction of the class.– If the endower appoints a specific time for the entitlement ofthe yield, the right of the endowment beneficiaries is establishedupon its occurrence.– If the endower appoints a specific place for delivering the yield,otherwise it is where the custom dictates its distribution.– Legitimacy of temporal and spatial preparation in the endowment.